MINIMUM WAGE IMPLICATIONS AND POVERTY NUMBERS EAST JAVA PROVINCE - Sari, Novi Primita (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2018)
An area is said to be advanced if the number of people living below the poverty line is getting smaller. But the problem of poverty is not an easy matter to solve, many factors that lead to faster growth every year. This study aims to analyze the implications of GDRP, the determination of regional minimum wages (UMR) and unemployment rates for the number of poor people in East Java Province. The method used in this study is a regression analysis with panel data covering, Regency and City GDRP data throughout the East Java Province, 2015 to 2016 UMR and unemployment in all Regency and City regions in East Java Province in the same two-year period. The results of the analysis of this study can be concluded that in the last two years the GDRP variables did not have an influence on poverty, but two variables, namely unemployment and regional minimum wages had an influence on the poverty rate in East Java Province. With the R square value obtained is 0.999483 which means that the model in this study is able to explain the phenomenon of 99.98 percent.